Georgia Architectural and Historic Properties Survey of 416 West Street, Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 416 West Street, Valdosta, Ga., December 1980. Small one story house with tin, gabled roof, full width shed porch with square posts. Shiplap siding. Exposed rafters. Double hung sash with 2/2 lights. Fair condition. Date of Construction: App. 1900-1910. Typical vernacular house in a district of similar houses of same age. Significant as part of a potential N.R. district.
Georgia Architectural and Historic Properties Survey of 416 West Street, Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 81.9 MB (85,881,762 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)